Pengembangan Multimedia Interaktif Sway pada Pembelajaran IPAS Kelas IV Sekolah Dasar : Development of Sway Interactive Multimedia in for Science Learning for The Fourth Graders of Primary School - Nesha Maulidia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research is motivated by the lack of use of interactive multimedia in learning. The aim of this research is to develop valid, practical and effective interactive multimedia. This research is included in the development research (R&D) ADDIE development model. The interactive multimedia created is then validated by validators consisting of material expert validation, media expert validation and language expert validation. The results of research on interactive multimedia development show that the validity of material in the very effective category is 95%, the validity of media in the very effective category is 99.16%, and the validity of language in the very effective category is 87.5%. The teacher questionnaire results were 95.83% in the very practical category, and the student questionnaire results were 91.02% in the very practical category. The test results produced effective interactive multimedia from the results of the test sheet work which showed an average increase with a percentage of 88.46%. Therefore, it can be concluded that Sway's interactive multimedia on energy transformation material around us in grade 4 elementary school is declared as valid, practical and effective interactive multimedia.